2009
DOI: 10.1007/s12275-008-0256-2
|View full text |Cite
|
Sign up to set email alerts
|

Induction of growth phase-specific autolysis in Bacillus subtilis 168 by growth inhibitors

Abstract: Growth phase-specific autolysis of Bacillus subtilis by inhibitors of membrane permeability, inhibitors of macromolecule biosynthesis, inhibitors of cell wall biosynthesis and detergents were tested and characterized in glucose limited liquid medium. The minimum autolysin induction concentration (MAIC) of test compounds, which was at least 1/20th lower than the conventional autolysis induction concentration, induced autolysis only for cells at the glucose exhaustion point (diauxic point) of the growth phase, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…A recent report showed that B. subtilis undergoes autolysis when exposed to antibiotics, including macrolides, during the diauxic transition (Chung et al 2009). We questioned whether chalcomycin A could contribute to the lysis of B. subtilis in co-culture with Streptomyces sp.…”
Section: Mg1 Maintains Lytic Activitymentioning
confidence: 99%
“…A recent report showed that B. subtilis undergoes autolysis when exposed to antibiotics, including macrolides, during the diauxic transition (Chung et al 2009). We questioned whether chalcomycin A could contribute to the lysis of B. subtilis in co-culture with Streptomyces sp.…”
Section: Mg1 Maintains Lytic Activitymentioning
confidence: 99%
“…B . subtilis is prone to autolysis due to environmental stressors or the regulated processes that occur at different stages of the cell life 31,32 . To find out the bioactive molecules, B .…”
Section: Resultsmentioning
confidence: 99%
“…Bacillus are complex organisms that exist as vegetative cells or metabolically inert spores or as part of a multicellular biofilm when encountering extreme environments 43 . When the environment is deficient in nutrients, rich in growth inhibitors and the pH or osmotic pressure is unfavorable, the vegetative cells of Bacillus are prone to autolysis, releasing resistant spores 31,32 . The above extreme conditions, to a large extent, can be provided by the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus subtilis PS-216 wt strain was grown in LB medium as described above and treated with 0.0125% (V/V) Triton X-100, 0.01% (w/V) SDS, 0.01% (w/V) cetyl trimethylammonium bromide (CTAB), 100 μg mL -1 ampicillin or 100 μg mL -1 kanamycin in the middle exponential phase at OD 650 between 0.4 and 0.5. Ampicillin was used as a positive control known to induce cell lysis, whereas kanamycin was used as a negative control ( Chung et al, 2009 ; Falk et al, 2010 ; Lacriola et al, 2013 ). Cell suspension was incubated further at 37°C and 200 rpm and OD 650 was measured every 30 min for 5 h. To determine the impact of different detergents on bacterial strain, the rate of lysis was calculated from measured decrease of OD 650 after treatment with antimicrobial agents.…”
Section: Methodsmentioning
confidence: 99%